Board gender diversity, board independence and firm performance in Malaysia - Kweh, Qian Long; Norazlin, Ahmad; Irene, Wei Kiong Ting; Zhang, Cheng; Hasahudin, Hassan (University of Malaya, 2019)
This study investigates the influences of board gender diversity and board independence on firm performance. Ordinary least squares, two-stage least squares and generalised method of moments are employed to test the relationships among board gender diversity, board independence, and firm performance in firms listed on Bursa Malaysia between 2010 and 2015. The regression results indicate that female directors and independent directors significantly and negatively affect firm performance, respectively. However, the interaction term of board gender diversity and board independence is statistically insignificant. Overall, managers must consider that board gender diversity and board independence may not have an interactive effect on improving the performance of their firms.